2022
DOI: 10.3389/fphys.2022.905795
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and cardiorespiratory responses to submaximal and maximal exercise in adults with Down syndrome

Abstract: Introduction: The genetic disorder causing Down syndrome (DS) affects the cardiorespiratory and hemodynamic parameters. When exercising, sufficient blood flow is necessary for active muscles. Cardiac output (Q) must be proportional to the peripheral requirements. In case the stroke volume (SV) is lower, the heart rate (HR) will increase further in order to maintain an adequate blood flow in the active territories (HR compensatory response). People with DS have a lower HR response to maximal exercise. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Adults with DS have lower cardiorespiratory responses than neurotypical adults [13] , so exercise interventions related to this objective are necessary. However, it is important to always take congenital heart disease into account in this population when prescribing exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adults with DS have lower cardiorespiratory responses than neurotypical adults [13] , so exercise interventions related to this objective are necessary. However, it is important to always take congenital heart disease into account in this population when prescribing exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Adults with Down syndrome tend to have negative alterations in health indicators and generally have higher rates of obesity than their typically developing peers [11] . They also have impaired physical fitness, expressed in lower strength [12] and aerobic capacity [13] compared to adults without Down syndrome. Furthermore, it has been reported that a large part of adults with DS are sedentary, and it is estimated that less than 10% of this population reaches the minimum recommendation for physical activity [14] [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Of these 45 tests, 41 used a treadmill protocol, and of those 41, the vast majority (29 out of 41) used a similar speed and incline protocol, all starting at an individualised walking speed at 0% incline, increasing the incline by 2.5% per step until 12.5% was reached, after which speed was increased until volitional exhaustion. These protocols did have minor variations in step duration: 21 protocols used 2-min steps (Baynard et al 2004;Fernhall et al 2005;Goulopoulou et al 2006;Baynard et al 2008;Cowley et al 2010;Cowley et al 2011;Ordonez et al 2014;Wee et al 2015;Boer & Moss 2016a,b;Boer 2017;Boer 2018;Mendonca et al 2018;Beck et al 2021;Oviedo et al 2021;Beck et al 2022;Oviedo et al 2022;Boer 2023;Dodd et al 2023), 1 protocol used 3-min steps (Climstein et al 1993), 4 protocols used 5-min steps until 7.5% incline and then 2-min steps from 7.5% to the end (Mendonca et al 2010;Mendonca et al 2010b;Mendonca et al 2011a,b), and 3 protocols used 4-min steps until 7.5% incline and 2-min steps from 7.5% to the end (Fernhall et al 2009;Mendonca et al 2022) (Climstein et al 1993).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The gold standard test for cardiorespiratory fitness is measuring peak oxygen uptake (VO 2 peak) during a maximal exercise test [American College of Sports Medicine (ACSM) 2022]. Maximal exercise testing has increasingly been applied to individuals with DS to investigate their response to acute and chronic exercise (Boer & Moss 2016a;Beck et al 2022;Oviedo et al 2022). The majority of these studies show a lower VO 2 peak in individuals with DS compared with the general population (Baynard et al 2008;Mendonca et al 2010b), although some other studies show a higher VO 2 peak in individuals with DS (Eberhard et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Low blood pressurehypotension -is common in both children and adults with DS [4][5][6] . This hypotension results in lower cardiorespiratory fitness and an inadequate blood pressure response to sub-maximal and maximal exercise 7,8 limiting the ability to participate in many activities 9 which in turn impacts quality of life. DS patients also commonly have non-dipping nocturnal blood pressure and heart rate which may contribute to sleep disorders and an increased risk of cardiovascular events [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%